Pengaruh Konsentrasi Maltodekstrin Terhadap Karakteristik Bubuk Strawberry Yang Berpotensi Mencegah Covid-19 Pada Lansia: Pengaruh Konsentrasi Maltodekstrin terhadap Karakteristik Bubuk Stroberi yang Berpotensi Mencegah COVID-19 pada Lansia - Mia Srimiati; Annisa Dinya Zahra; Febry Harsanti; Putri Habibah; Alfisah Ratu Maharani (Amerta Nutrition, 2023)
Background: The strawberry is an antioxidant-rich fruit with the potential to prevent COVID-19, especially in the elderly. However, the fruit's high-water content makes it susceptible to decay and diminishes its quality. Product diversification into instant powder with a spray drying method and the addition of maltodextrin is one possible solution. Objectives: The purpose of this study is to examine the effect of maltodextrin concentration on the physical properties of strawberry powder produced by spray drying. Methods: The experimental study employed a completely randomized design and three maltodextrin concentrations: P1 (20%), P2 (25%), and P3 (30%). Organoleptic data were gathered using a questionnaire with a 1 to 9 hedonic scale scoring method. 35 students from the sixth and eighth semesters of Nutrition at Binawan University served as panelists. Results: The addition of maltodextrin to strawberry powder significantly altered the powder's flavor, aroma, texture, and color. The solubility test revealed that the strawberry powders P1, P2, and P3 were water-soluble. The selected strawberry powder contained 5.08% moisture, 1.05% ash, 1.13% protein, 0.02% fat, and 92.73% carbohydrates, according to approximative analysis results. The results revealed that the antioxidant levels of P1 (20%), P2 (25%), and P3 (30%) were 7.95 ppm, 8.07 ppm, and 8.36 ppm, respectively. Conclusions: When added, maltodextrin at a concentration of 30% produces the best possible physical properties.